ASSOCIATION OF PERCEIVED STRESS AND COPING STRATEGIES WITH DEPRESSIVE SYMPTOMS IN STUDENTS AT A PRIVATE MEDICAL COLLEGE IN ISLAMABAD - Sawera Mansoor (Army Medical College Rawalpindi, 2021)
Objective: To determine the association of perceived stress and coping strategies with depressive symptoms in students at a private medical college in Islamabad.